Empathic tendency, majority culture representation, and political conservatism as predictors of intercultural sensitivity - (:unkn) unknown (Immigrant Institutet, 2018)
This study aims to determine the variables capable of predicting the concept of intercultural sensitivity. For this reason, it uses correlational survey model. The participants in this study were the prospective primary school teachers studying in Dicle and Marmara Universities in Turkey. This study employed basically three tools for data collection-namelyPersonal Information Form, Empathetic Tendency Scale, and Intercultural Sensitivity Scale. Hierarchical multiple regression analysis was employed to analyze the data obtained in this study. According to the results obtained in this research, individuals’ empathetic, sympathetic and egocentric tendencies, their properties representing the majority culture, and their levels of political conservatism account for 23.8% of their levels of intercultural sensitivity. © 2018, Immigrant Institutet. All rights reserved.
Keywords: Empathy; Intercultural sensitivity; Majority culture; Political conservatism